Comparative effects of atorvastatin 80 mg versus rosuvastatin 40 mg on the neutrophil to lymphocyte ratio, platelet to lymphocyte ratio and monocyte to HDL-cholesterol ratio in patients with acute myocardial infarction (Annals of Medical Research, 2021)
Aim: Previous studies have shown the association between the elevated levels of hematological markers like Neutrophil to Lymphocyte ratio (NLR), Platelet to lymphocyte ratio (PLR) and Monocyte to High density lipoprotein cholesterol (HDL-C) ratio (MHR) and increased risk of the existence of cardiovascular disease, increased risk of acute coronary syndromes and severity of cardiovascular disease. One of the most commonly used drugs in atherosclerotic cardiovascular diseases are statins and we know that statins have beneficial effects in addition to LDL-lowering effects known as pleiotropic effects. However the effects of statins on the hematological markers are unclear. We performed this investigation to clarify and compare the effects of maximum-dose of atorvastatin and rosuvastatin on hematological biomarkers in patients with acute myocardial infarction.Methods: Statin or other anti-lipid drugs naive patients with either ST-segment elevation myocardial infarction or Non-ST elevation myocardial infarction were enrolled to our study. Biochemistry parameters, lipid parameters, blood-count parameters and NLR, PLR and MHR levels were measured at baseline and 30 days after discharge. Baseline characteristics and results of 2 groups after one-month treatment were compared.Results: Among the 128 statin-naive patients included, 65 patients received atorvastatin (80 mg/day) and 63 patients recieved rosuvastatin (40 mg/day). Baseline clinical characteristics of groups were similar. Atorvastatin 80 mg significantly decreased the levels of NLR (p=0.001) and MHR (p=0.024) at the end of one-month therapy. Rosuvastatin 40 mg also significantly decreased the levels of NLR (p=0.001) and MHR (p=0.006) at the end of one-month therapy. Both statins were ineffective on the levels of PLR. Percent and absolute changes of NLR, MHR and PLR were similar and there were no statistically significant differences between both groups. The percent and absolute changes of lipid parameters were also similar among both treatment arms.Conclusion: Our results showed that atorvastatin 80 mg and rosuvastatin 40 mg decreased the NLR and MHR levels significantly at the end of one-month therapy. However, both statins have no effects on PLR levels.Keywords: Acute myocardial infarction, atorvastatin, monocyte-to-HDL-cholesterol ratio, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, rosuvastatin.
Keywords: Acute myocardial infarction, atorvastatin, monocyte-to-HDL-cholesterol ratio, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, rosuvastatin.